Fabrication of a novel electrochemical sensing platform based on a core–shell nano-structured/molecularly imprinted polymer for sensitive and selective determination of ephedrine. Issue 56 (25th May 2016) - Bagheri, H.; Pajooheshpour, N.; Afkhami, A.; Khoshsafar, H.
Abstract : A simple methodology was used to develop a novel sensor based on a core–shell/molecularly imprinted polymer (MIP) for the determination of ephedrine. Abstract : A simple methodology was used to develop a novel sensor based on a core–shell/molecularly imprinted polymer (MIP) for the determination of ephedrine. The Fe3 O4 @SiO2 @TiO2 -MIP nanocomposite with a well-defined core–shell structure was synthesized using a simple imprinting strategy. The morphology of the synthesized nanocomposite was observed by scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy and the properties of the sensor were examined by cyclic voltammetry and electrochemical impedance spectroscopy. The fabricated electrochemical sensor based on the Fe3 O4 @SiO2 @TiO2 -MIP nanocomposite exhibits great features such as a remarkably low detection limit of 0.0036 μmol L −1 (3 S b / m ), superb selectivity in discriminating ephedrine from its structural analogues and good anti-interference ability towards several co-existing substances. Also, it was used to detect the concentration of ephedrine in the linear range of 0.0090–2.8 μmol L −1 . Moreover, the proposed method demonstrates excellent repeatability and stability, with a relative standard deviation (RSD) of less than 1.4% and 1.6%, respectively. Analysis of ephedrine in pharmaceutical dosage forms and biological fluids is successfully carried out without the assistance of complicated pretreatment. The Fe3 O4 @SiO2 @TiO2 -MIP nanocomposite presented here with admirable merits makes it a promising candidate for developing an electrochemical sensor device to perform routine analysis of ephedrine.